(untitled) (Nexo Revista Científica, 2021)
The use of modern means of mechanization of loading and unloading operations in places of mass processing of bulky loads in railway and water connection allows to increase the efficiency and productivity of various types of transport, to ensure the safety of load and rolling stock. The most common method of unloading open wagons in ports, mining enterprises, thermal power plants, etc. is the use of special rotary car dumpers. However, it should be noted that unloading on the car dumpers leads to damage of the carriages structural elements. The article presents the results of strength calculations of the car dumper body under the influence of specified dynamic loads from the expiring cargo. They show that the safety margin of the load-bearing elements of the car body is not enough at critical corners of rotation of the car dumper rotor. The studies were carried out using modern computer modeling methods used in the development of new-generation freight car designs. The software package took into account the effects of dynamic loading as external factors that occur at different corners of the car dumper rotor. The implementation of the results obtained at the design stage of innovative structures of open wagon car bodies will allow predicting the operational parameters of load-bearing structures. The presented studies are aimed at improving the safety and operational reliability of the cargo car fleet.